Numerical analysis of bio-digester substrate heating methods. (2022) - Ashin, KK.; Arun Chandran, P.; Hareesh Krishnan, H.; Glivin, Godwin; Premalatha, M.; Mariappan, V.; Sekhar, Joseph
Abstract: Biogas is a renewable fuel produced by anaerobic digestion of biomass. The performance of anaerobic digestion depends on many factors in which temperature is one of the important parameter. The biogas production rate and yield varies according to the temperature of the substrate. The present work focuses on the importance of temperature in biogas generation from anaerobic digestion and also to compare different in-direct heating methods using ANSYS Fluent K-Epsilon model. The different substrate heating methods are Floor heating, In-vessel heating, and On-vessel heating which can be incorporated into conventional domestic digesters to heat the substrate to the desired optimum temperature for enhanced microbial activity and thereby increased biogas production. Different heating sources are used to heat the slurry like electric coil to heat the circulating fluid and in the case of domestic scale bio digester, solar energy can be utilised. Solar water heater incorporated with a storage system would be appropriate. From the numerical analysis, Floor heating method gave about 5 °C rise in temperature of the slurry and On-vessel showed 5–6 °C rise in temperature and In-vessel showed 6–7 °C rise in temperature of the substrate and was found to be more efficient than other heating methods because it can distribute heat more uniformly to the substrate.